2015
DOI: 10.3348/kjr.2015.16.6.1303
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Diffusion Tensor Imaging for Diagnosing Cervical Spondylotic Myelopathy in Patients Showing Spinal Cord Compression

Abstract: ObjectiveTo assess the performance of diffusion tensor imaging (DTI) for the diagnosis of cervical spondylotic myelopathy (CSM) in patients with deformed spinal cord but otherwise unremarkable conventional magnetic resonance imaging (MRI) findings.Materials and MethodsA total of 33 patients who underwent MRI of the cervical spine including DTI using two-dimensional single-shot interleaved multi-section inner volume diffusion-weighted echo-planar imaging and whose spinal cords were deformed but showed no signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Further, spinal cord T2 hyperintensity is considered an important risk factor by the spine care community (Wilson et al, 2013), and diffusion tensor imaging (DTI) parameters have shown the capacity to differentiate cervical myelopathy patients not only from normal individuals (Chen et al, 2016;Guan et al, 2015;Lee et al, 2015) but also from nonmyelopathic cervical cord compression cases (Kerkovsky et al, 2012), and further to correlate with severity of myelopathy (Rajasekaran et al, 2014), the segments of the cervical cord involved (Suetomi et al, 2016), and to predict postsurgical outcome (Arima et al, 2015). A re-evaluation of the predictive model describing the risk of progression of NMDCCC to symptomatic myelopathy (Bednarik et al, 2008) was thus indicated, in a sample also including completely asymptomatic subjects with less severe stages of degenerative cervical cord compression and with the use of DTI parameters to validate the previous model.…”
Section: Introductionmentioning
confidence: 99%
“…Further, spinal cord T2 hyperintensity is considered an important risk factor by the spine care community (Wilson et al, 2013), and diffusion tensor imaging (DTI) parameters have shown the capacity to differentiate cervical myelopathy patients not only from normal individuals (Chen et al, 2016;Guan et al, 2015;Lee et al, 2015) but also from nonmyelopathic cervical cord compression cases (Kerkovsky et al, 2012), and further to correlate with severity of myelopathy (Rajasekaran et al, 2014), the segments of the cervical cord involved (Suetomi et al, 2016), and to predict postsurgical outcome (Arima et al, 2015). A re-evaluation of the predictive model describing the risk of progression of NMDCCC to symptomatic myelopathy (Bednarik et al, 2008) was thus indicated, in a sample also including completely asymptomatic subjects with less severe stages of degenerative cervical cord compression and with the use of DTI parameters to validate the previous model.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the DTA studies, one reviewer experienced in DTA studies selected eligible articles according to criteria established elsewhere ( 9 ) with additional confirmation by another DTA expert in cases of ambiguity. Of the initial 124 candidate articles, 63 articles ( 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 ) were finally included. Regarding the studies that analyzed reliability, eligible articles were chosen by consensus after review by two of four independent reviewers experienced in the relevant methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Seungbo Lee і співавт., після аналізу результатів МРТ пацієнтів з компресійною мієлопатією на рівні ШВХ, виявили, що величина FA знижується паралельно зі збільшенням ступеня стенозу хребтового каналу [13]. У низці досліджень продемонстровано клінічну кореляцію між зменшенням значення FA і тяжкістю ХСМТ [14].…”
Section: вступunclassified